Load-carrying capacity of housings in solid timber beams - Shams Huq, Rafid; Heal, Tyler; Tannert, Thomas (Maderas. Ciencia y Tecnología, 2025)
Timber framing has traditionally relied on metal fasteners, with have a high carbon footprint and often limited aesthetic appeal. These challenges can be addressed by using traditional joints such as timber housings. However, there are no design guidelines available that account for the joint geometric parameters, mechanical reinforcements, or the wood moisture content during fabrication and when loaded. In this research, the influence of joint geometry, wood moisture and reinforcement on the load-carrying capacity of solid timber beams with housings was investigated. A total of 150 Pseudotsuga menziesii (Douglas fir) beams were tested according standard, considering different moisture condition (wet or dry) at the time of cutting and at the time of testing. The tests confirmed that greater bearing depth and the use of self-tapping screws as reinforcement lead to increased load-carrying capacity. However, moisture condition significant affected only the double housings, not the single housings. In addition, 198 small-scale specimens were tested for shear, tension and compression to evaluate the impact of small clear specimen material strength on the beam load-carrying capacity. The results showed that these properties were weak predictors of housing performance. Finally, a design approach based on existing Canadian code provisions is suggested.